Prowadzenie przedsiębiorstwa w spadku – zagadnienia wybrane - Wrzecionek, Rafał (PRAWO i WIĘŹ, 2026)
The death of a sole proprietorship results in the entry of their business into its final phase of existence, in which the business is considered an inherited enterprise. The regulations analyzed in this study stem primarily from the Succession Management Act, in force since November 25, 2018, as amended by the Act of July 31, 2019, amending certain acts to reduce regulatory burdens. This Act regulates, among other things, the principles of temporary management of a business following the death of an entrepreneur who conducted business activity in their own name based on an entry in the Central Register and Information on Business Activity. The institution responsible for managing a business inherited is succession management, performed by a succession administrator. The administrator undertakes actions that impact not only the assets of the owners of the inherited business but also the inherited business itself. The aim of the considerations undertaken is to analyze an issue that is also important in practice – the scope of the concept of “running an enterprise in an inheritance” and undertaking activities “resulting from the business activity carried out by the deceased entrepreneur”.